VD_FINDINFO Décision / 2013 / 805 vom 23. September 2013 - VD Tribunal cantonal (2013)
FRAIS DE LA PROCÉDURE, DÉCISION SUR FRAIS, FRAIS JUDICIAIRES, DÉPENS | 69 al. 1bis LAI, 61 let. a LPGA, 49 LPA-VD, 51 LPA-VD, 94 al. 1 let. a LPA-VD